The Role of Product Innovation and Market Orientation on the Competitiveness of Micro Businesses in the Digital Economy Era in Kendari City - Imran; Ridha Taurisma Lajaria; Grace Permatasari Tandipayuk (Universitas Sulawesi Barat, 2026)
The transformation of the digital economy has changed the competitive landscape of micro enterprises by increasing market openness and the intensity of technology-based competition. In this context, product innovation and market orientation are seen as strategic factors that can strengthen the competitiveness of micro businesses. This study aims to analyze the influence of product innovation and market orientation on the competitiveness of micro businesses in the digital economy era. The study uses a quantitative approach with primary data obtained through a Likert scale questionnaire on 40 micro enterprises in Kendari City that have adopted digital marketing channels. The analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS) to test the partial and simultaneous relationships between variables. The results show that product innovation and market orientation have a positive and significant effect on the competitiveness of micro enterprises, both individually and together, with a strong contribution of the model in explaining the variation in competitiveness. These findings confirm that the ability to develop products sustainably and responsiveness to the needs of digital consumers are the main determinants of competitive advantage at the micro business level. This research contributes to enriching the literature on strategic management and digital entrepreneurship and provides an empirical basis for the formulation of innovation-based and market-oriented MSME development strategies in the digital economy era